Gadolinium-Enhanced T2 FLAIR Is an Imaging Biomarker of Radiation Necrosis and Tumor Progression in Patients with Brain Metastases - Heyn, Chris; Bishop, Jonathan; Moody, Alan R.; Kang, Tony; Wong, Erin; Howard, Peter; Maralani, Pejman; Symons, Sean; MacIntosh, Bradley J.; Keith, Julia; Lim-Fat, Mary Jane; Perry, James; et al. (American Journal of Neuroradiology, 2025)
BACKGROUND AND PURPOSE: Differentiating radiation necrosis (RN) from tumor progression (TP) after radiation therapy for brain metastases is an important clinical problem requiring advanced imaging techniques that may not be widely available and are challenging to perform at multiple time points. The ability to leverage conventional MRI for this problem could have a meaningful clinical impact. The purpose of this study was to explore contrast-enhanced T2 FLAIR (T2FLAIRc) as a new imaging biomarker of RN and TP.MATERIALS AND METHODS: This single-institution retrospective study included patients with treated brain metastases undergoing DSC-MRI between January 2021 and June 2023. Reference standard assessment was based on histopathology or serial follow-up, including the results of DSC-MRI for a minimum of 6 months from the first DSC-MRI. The index test was implemented as part of the institutional brain tumor MRI protocol and preceded the first DSC-MRI. T2FLAIRc and gadolinium-enhanced T1 (T1c) MPRAGE signal were normalized against normal brain parenchyma and expressed as a z score. The mean signal intensity of enhancing disease for the RN and TP groups was compared using an unpaired t test. Receiver operating characteristic curves and area under the receiver operating characteristic curve (AUC) were derived by bootstrapping. The DeLong test was used to compare AUCs.RESULTS: Fifty-six participants (mean age, 62 [SD, 12.7] years; 39 women; 28 with RN, 28 with TP) were evaluated. The index MRI was performed, on average, 73 [SD, 34] days before the first DSC-MRI. Significantly higher z scores were found for RN using T2FLAIRc (8.3 versus 5.8, P < .001) and T1c (4.1 versus 3.5, P = .02). The AUC for T2FLAIRc (0.83; 95% CI, 0.72–0.92) was greater than that for T1c (0.70; 95% CI, 0.56–0.83) (P = .04). The AUC of DSC-derived relative CBV (0.82; 95% CI, 0.70–0.93) was not significantly different from that of T2FLAIRc (P = .9).CONCLUSIONS: A higher normalized T1c and T2FLAIRc signal intensity was found for RN. In a univariable test, the mean T2FLAIRc signal intensity of enhancing voxels showed good discrimination performance for distinguishing RN from TP. The results of this work demonstrate the potential of T2FLAIRc as an imaging biomarker in the work-up of RN in patients with brain metastases.AUCarea under the receiver operating characteristic curveIQRinterquartile rangerCBVrelative CBVRNradiation necrosisROCreceiver operating characteristicSRSstereotactic radiosurgeryT1ccontrast-enhanced T1T2FLAIRccontrast-enhanced T2 FLAIRTPtumor progression